Contribution of the TIME in BCP-ALL: the basis for novel approaches therapeutics - Poveda-Garavito, Nathaly; Combita, Alba Lucía (Frontiers in Immunology, 2024)
The bone marrow (BM) niche is a microenvironment where both immune and non-immune cells functionally interact with hematopoietic stem cells (HSC) and more differentiated progenitors, contributing to the regulation of hematopoiesis. It is regulated by various signaling molecules such as cytokines, chemokines, and adhesion molecules in its microenvironment. However, despite the strict regulation of BM signals to maintain their steady state, accumulating evidence in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) indicates that leukemic cells can disrupt the physiological hematopoietic niche in the BM, creating a new leukemia-supportive microenvironment. This environment favors immunological evasion mechanisms and the interaction of these cells with the development and progression of BCP-ALL. With a growing understanding of the tumor immune microenvironment (TIME) in the development and progression of BCP-ALL, current strategies focused on “re-editing” TIME to promote antitumor immunity have been developed. In this review, we summarize how TIME cells are disrupted by the presence of leukemic cells, evading immunosurveillance mechanisms in the BCP-ALL model. We also explore the crosstalk between TIME and leukemic cells that leads to treatment resistance, along with the most promising immuno-therapy strategies. Understanding and further research into the role of the BM microenvironment in leukemia progression and relapse are crucial for developing more effective treatments and reducing patient mortality.